(untitled) (Journal of actual problems of jurisprudence, 2019)
This article discusses the possibility of using mediation to resolve labor disputes. The practical application of mediation in foreign countries. The analysis of the historical roots of mediation in the Republic of Kazakhstan. Particular attention is given to the institution biys in traditional Kazakh society as the basis of modern mediation. Practical recommendations for change in the Labour Code of the Republic of Kazakhstan and the Law on Mediation. Keywords: mediation, labor disputes, the institute biys, mediation, labor disputes, pre-trial settlement.